Toxicity and Sublethal Effect of Chlorantraniliprole on Multiple Generations of Aedes aegypti L. (Diptera: Culicidae) - Nimra Batool; Muhammad Abubakar; Ahmed Noureldeen; Muhammad Nadir Naqqash; Akram Alghamdi; Zamzam M. Al Dhafar; Fadi Baakdah; Raimondas Mozūratis (Insects)
Due to the quick development of insecticide resistance, it is crucial to optimize management programs by understanding the sublethal effects of effective insecticides like chlorantraniliprole on Aedes aegypti L. populations. Using age-stage and two-sex life tables, we investigated the sublethal impacts of chlorantraniliprole on Ae. aegypti. Larval duration in the progeny of exposed parents was reduced by 0.33–0.42 days, whereas, the longevity of male and female adults was decreased by 1.43–3.05 days. Similarly, the egg-laying capacity of F1 and F2 progeny of the exposed parents was significantly reduced from 27.3% to 41.2%. The mean generation time (T) increased up to 11.8% in exposed populations, and the net reproduction rate (Ro) decreased by 51.50–55.60%. After 24 h of chlorantraniliprole treatment, there was a significant increase in cytochrome P450 activity. Contrarily, the activity of glutathione S-transferase (GST) initially declined but started increasing after 48 h of treatment. This research highlights the importance of chlorantraniliprole in mosquito management, as well as the importance of considering sublethal effects when developing strategies to handle them. Having a thorough understanding of the harmful effects of insecticides on mosquito populations can greatly enhance the effectiveness of insecticide-based interventions, while also minimizing the risk of pest resurgence.